Activity-dependent adaptations in inhibitory axons - Frias, Cátia P.; Wierenga, Corette J. (Frontiers in Cellular Neuroscience, 2013)
Synaptic connections in our brains change continuously and throughout our lifetime. Despite ongoing synaptic changes, a healthy balance between excitation and inhibition is maintained by various forms of homeostatic and activity-dependent adaptations, ensuring stable functioning of neuronal networks. In this review we summarize experimental evidence for activity-dependent changes occurring in inhibitory axons, in cultures as well as in vivo. Axons form many presynaptic terminals, which are dynamic structures sharing presynaptic material along the axonal shaft. We discuss how internal (e.g. vesicle sharing) and external factors (e.g. binding of cell adhesion molecules or secreted factors) may affect the formation and plasticity of inhibitory synapses.